The Relationship Household Environmental Sanitation with Incidence of Stunting in Toddlers: Literature Review - Wakhid Anwar; Nurjazuli Nurjazuli; Tri Joko (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Stunting (Short Children) one of the nutritional problems faced in the world, especially in poor and developing countries. Stunting is a problem because the impact it has can affect the quality of human resources and be detrimental to the world of health, including increasing morbidity and mortality rates. Sub optimal brain development results in delay in motor skills and mental growth. Many studies have been conducted on the risk factors for stunting in toddlers, including environmental sanitation which is an indirect cause stunting incident. Objective: The Study aims to describe relationship between household environmental sanitation with the incidence of stunting toddlers. Method: This research uses a systematic review method to summarize research results over the last 5 years. The data source comes from Indonesian Environmental Health Journal and the google scholar jurnal with the keywords “Stunting and environment”. The selected articles are results of research related to environmental sanitation factors and behavior that cause stunting. Result: There are 7 for 10 research article showed a significant relationship between household environmental sanitation and the incidence of stunting in toddlers. Conclusion: Based on the results of studies conducted in 10 Journals, information was obtained that those related to the incidence of stunting in toddlers include acces to clean water and drinking water, unhealthly latrines, food intake, processing of waste and household liquid waste that does not requirements, mother’s education level, parenting pattern for toddlers, exclusive breastfeeding and incidence of infection or diarrhea.